Land tenure systems and agricultural innovation. The case of alley farming in Nigeria - Francis, P.A. (Elsevier, 1987)
Discusses the implications of land tenure systems in south-east Nigeria for the acceptability and viability of alley farming. Reviews the region's tenure system followed by case studies of the communities where the Humid Zone Programme of ILCA has been conducting on-farm trials of alley farming. The studies consists of brief accounts of the communities' social constitutions and farming system.